2009
DOI: 10.1021/ie801240q
|View full text |Cite
|
Sign up to set email alerts
|

Solid−Liquid Catalytic Reactions in a New Two-Impinging-Jets Reactor: Experiment and Modeling

Abstract: Novel type of two-impinging-jets loop reactor (TIJLR) has been proposed and tested successfully for the solid-liquid catalytic reactions. The TIJLR was tested using the catalytic reaction of isomerization of D-glucose to D-fructose by immobilized glucose isomerase catalyst as a typical model system of solid-liquid catalytic reactions. The TIJLR is characterized by a high intensity reaction chamber, which is separated by a perforated plate from other parts of the reactor. The perforated plate was used as a filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In a subsequent study, the same group investigated another variation on the TIJR theme whereby the reactor included a perforated plate designed to retain the IGI particles within the high-intensity mixing zone region of the reactor. 93 The authors concluded that the jet Reynolds number was one of the more important parameters for predicting TIJLR performance.…”
Section: Immobilized Glucose Isomerase Processesmentioning
confidence: 99%
“…In a subsequent study, the same group investigated another variation on the TIJR theme whereby the reactor included a perforated plate designed to retain the IGI particles within the high-intensity mixing zone region of the reactor. 93 The authors concluded that the jet Reynolds number was one of the more important parameters for predicting TIJLR performance.…”
Section: Immobilized Glucose Isomerase Processesmentioning
confidence: 99%
“…Momentum transport and reaction engineering aspects of confined micromixers with impinging jet and vortex geometries have recently been studied in great detail. These have been applied to synthesize a variety of particles, in particular, for drug delivery and medical engineering. ,, Confined impinging streams merging inside closed channels have been applied to solid/liquid catalytic reactions, to polystyrene particle formation, and for the reactive in situ generation of block copolymers to protect colloidal particles . Moreover, this stream configuration is also of interest for emulsion formation …”
Section: Introductionmentioning
confidence: 99%
“…To avoid clogging, a design with 10° downward feed jets was selected in most of the literature . This feed method can avoid the two fluids from direct frontal collision.…”
Section: Resultsmentioning
confidence: 99%